Adopting the rights-based model: Music multinationals and local music industries since 1945 - Bakker, Gerben (Popular Music History, 2012)
This article identifies four economic tendencies that shaped the development of the international recorded music industry since 1945: the importance of endogenous sunk costs led to a quality race; the fact that marginal revenue equalled marginal profit led to extreme vertical integration; the quasi-public good character of music its non-diminishability but partial excludability led to a sharply unequal income distribution among stars and the pioneering of new business models to transform consumer into producer surplus; and finally, the project based character of music production led to decentralized agglomeration. What can be characterized as rights-based multinationals emerged as a response to these forces. They married extreme vertical integration and a portfolio of A&R labels having limited economies of scale and scope, with a global distribution and marketing machine. This article tries to explain how they emerged and how they can explain increasing industrial concentration in the face of sharp growth of the market and of musical diversity.